Compensação da emissão de gases de efeito estufa na produção leiteira: o caso da integração pecuária-floresta na Fazenda Santa Bárbara em Quirinópolis - GO - Siqueira, Matheus Mentone de Britto (2025)
The Integrated Livestock-Forestry Systems (ILF) are indicated by the Brazilian government as a strategy capable of offsetting 37.9 million Mg of CO2 eq. by the year 2030. The objective of this study is to estimate the potential of an integrated livestock-forestry system to offset emissions from milk production on a family farm (Fazenda Santa Barbara) located in the southern region of the state of Goiás. To this end, greenhouse gas (GHG) emissions in the milk production process were estimated using the Cool Farm Tool (CFT), a GHG emissions calculator in several production systems at the farm level, whose input data were collected through questionnaires and field surveys carried out in the years between 2019/2020 and 2022/2023. Soil carbon (C) stocks under and between rows of eucalyptus trees were determined 4 years after IPF implementation and in the trees at 32 months and 101 months after IPF implementation. An area under continuous pasture next to the IPF was used as a reference to represent the status quo of C stocks in the sandy soil (sand ~73%) of the property before IPF implementation. Total GHG emissions due to milk production on the property were estimated by the CFT at 326.55 Mg CO2 eq in the 2019/2020 period, and 267.37 Mg CO2 eq in the 2022/2023 period. The emission intensity, or amount of carbon dioxide equivalent emitted (CO2 eq.) per unit of protein produced (Fat Protein Corrected Milk-FPCM), was 1.01 kg CO2 eq./ kg FPCM in 2019/2020 and 0.69 kg CO2 eq./ kg FPCM in 2022/2023. In relation to the reference pasture area, the C stock was 9 Mg ha-1 higher under eucalyptus tree rows in the IPF in the 0.0-1.0 m soil layer in 2019/20. The C compensation rate was calculated considering the growth and C stock in the trunk of eucalyptus trees since the implementation of the IPF in 2016, while the total GHG emissions from milk production and the C stock measured in the soil were considered fixed parameters based on the averages observed between 2020 and 2023. The forest component of the IPF was able to store 8.271 Mg ha-1 year-1 at 32 months and 31.30 Mg ha-1 year-1 at 101 months. The C compensation rate increases over the years proportionally to the growth of the forest component. In the first and second years after the implementation of the IPF system, approximately 9.9% of the total emissions from milk production on the property were offset by C capture in the soil and eucalyptus trees. In the third year, the GHG emission offset increased to 19.6%. Between the fourth and sixth years, compensation was 39.1% and from the seventh to the eighth year, 47.1%. From this study, it was possible to verify the GHG mitigation capacity of the IPF in dairy farming systems.